Production process of UHMW-PE film with conductivity

Through high-speed centrifugal mixing and high-temperature and high-pressure sintering processes, the problem of insufficient uniformity and performance of UHMW-PE film on black rubber tubes and conveyor belts is solved, the conductivity and UV resistance are improved, and the adhesion to rubber is improved. performance.

CN119261264APending Publication Date: 2025-01-07SUZHOU YIDIANDAO MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411588499.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When used in black rubber tubes and black conveyor belts, the existing UHMW-PE film is mixed with toner or masterbing for poor color uniformity. The overall conductivity, UV resistance and adhesion to rubber cannot meet the needs of users. .

Method used

The UHMW-PE raw material powder is uniformly mixed with conductive carbon black or superconducting carbon black powder by using a high-speed centrifugal mixer, and then high-temperature and high-pressure sintering and turning out the rolling process to form a black UHMW-PE film with conductive properties.

Benefits of technology

The conductive and UV resistance of UHMW-PE films are improved, and the adhesion performance with rubber is improved, solving the problems of uniformity and insufficient performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119261264A_ABST
    Figure CN119261264A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of production processes, in particular to a production process of a UHMW-PE (Ultra High Molecular Weight-Polyethylene) film with conductivity, which comprises the following steps: step 1, preparing raw materials; step 2, uniformly mixing; thirdly, powder die casting is conducted; 4, high-temperature and high-pressure sintering; step 5, naturally cooling; sixthly, turning and coil discharging are conducted; according to the UHMW-PE thin film, conductive carbon black or superconductive carbon black powder is added into UHMW-PE raw material powder and uniformly mixed in a high-speed centrifugal mixing mode, and the carbon black powder has a certain lubricating effect, so that the powder can be directly, efficiently and stably mixed and processed; the black UHMW-PE film has the advantages that the UHMW-PE raw material powder is added with the high-structure conductive carbon black powder, so that the processed black UHMW-PE film not only keeps the original product characteristics, but also has certain conductivity and UV resistance, meanwhile, the adhesion property with rubber is improved compared with that with the ordinary color, and if the high-structure conductive carbon black powder is added into the UHMW-PE raw material powder, the UHMW-PE film can be used for preparing the high-performance black UHMW-PE film. And the processed black UHMW-PE film has a good antistatic property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of production technology, and in particular to a production process of a UHMW-PE film with conductive properties. Background Art

[0002] UHMW-PE film, that is, ultra-high molecular weight polyethylene film, is made of UHMW-PE powder. The natural color of UHMW-PE powder is white and translucent, so the UHMW-PE film made is also white and translucent.

[0003] The UHMW-PE film currently used in black rubber tubes and black conveyor belts is black. The color of the UHMW-PE film itself is white and translucent. If color is required, the UHMW-PE film is generally mixed with color powder or masterbatch, but the uniformity of the mixture will be relatively poor, and its overall conductivity, UV resistance and its adhesion to rubber cannot meet the needs of users.

[0004] Therefore, when the above-mentioned UHMW-PE film is used in black rubber tubes and black conveyor belts, the UHMW-PE film is generally mixed with color powder or masterbatch for coloring, and its uniformity will be relatively poor. The overall conductivity, UV resistance and adhesion performance with rubber cannot meet the needs of users. A UHMW-PE film production process with conductive properties can be designed, which not only maintains the original product characteristics, but also increases certain UV resistance and conductivity. At the same time, the adhesion performance with rubber is also improved than that of ordinary natural colors. Summary of the invention

[0005] In order to overcome the problem that the existing black UHMW-PE film is colored by mixing UHMW-PE film with color powder or masterbatch, its uniformity will be relatively poor, and the overall conductivity, UV resistance and adhesion performance with rubber cannot meet the needs of users.

[0006] The technical solution of the present invention is: a process for producing a UHMW-PE film with conductive properties, the steps of which are as follows:

[0007] Step 1: Raw material preparation

[0008] First, prepare the raw material powder and carbon black powder of UHMW-PE. The carbon black powder can be conductive carbon black or super conductive carbon black.

[0009] Step 2: Mix evenly

[0010] Put the UHMW-PE raw material powder and 3.2%-3.8% carbon black powder into a high-speed centrifugal mixer. Start the high-speed centrifugal mixer. The internal stirring device will rotate at a high speed to generate a strong centrifugal force to fully mix the two powders. The mixing time is between 10-20 minutes, until the powder mixture reaches a uniform black color and there is no obvious particle separation phenomenon;

[0011] Step 3: Powder die casting

[0012] Pour the powder mixture mixed evenly in step 2 into the pre-prepared die-casting mold. After the powder is poured into the mold, a scraper or vibrator is needed to flatten and compact the powder surface to ensure uniform density and size of the blank.

[0013] Step 4: High temperature and high pressure sintering

[0014] The mold filled with powder is placed in a high-temperature and high-pressure sintering furnace for sintering. The sintering temperature is 280 degrees and the pressure is 100 kilograms per square centimeter. Under the combined effects of high temperature and high pressure, the powder particles gradually soften and fuse with each other to form a dense blank.

[0015] Step 5: Natural cooling

[0016] After sintering, the blank is placed in a natural cooling environment for cooling. During the cooling process, the state of the blank needs to be checked regularly to ensure that its internal mechanism is dense and has no obvious defects, so that the blank can be cooled down in a slow and uniform temperature change to avoid internal stress and cracks caused by rapid cooling;

[0017] Step 6: Turning the coil

[0018] The cooled cylindrical blank is put into the machine for turning process. During the processing, the blank is fixed on the lathe, and the cutting tool cuts the blank at a certain speed and feed rate, gradually processing it into the required film thickness. After the cutting is completed, the film is collected and wound into a roll for subsequent storage and transportation.

[0019] Preferably, the carbon black powder may be a highly structured conductive carbon black.

[0020] Preferably, before pouring the powder mixture in step three, a layer of release agent needs to be applied inside the die-casting mold so that the sintered blank can be smoothly demoulded.

[0021] Preferably, the sintering time in step 4 is determined according to the characteristics of the powder and the performance of the sintering furnace, and the sintering time ranges from 5 to 12 hours.

[0022] Preferably, in step five, due to the rapid temperature change at the initial stage of cooling, the interior of the blank may be experiencing a large stress change, so more frequent inspections are required, set to be checked every hour or every two hours, so as to promptly discover and deal with possible problems.

[0023] Preferably, in step five, as the blank is gradually cooled, its internal stress tends to be stable, and at this time the inspection frequency can be appropriately reduced to once every half a day or every day.

[0024] Preferably, in step five, the appearance of the blank needs to be visually inspected to see if there are cracks, deformation or abnormal color. Different parts of the blank are gently tapped with a small hammer, and the density and internal defects of the blank are judged by listening to the sound. If the sound is crisp and uniform, it may indicate that the inside of the blank is dense and has no obvious defects. If the sound is dull or hollow, there may be a problem.

[0025] Preferably, in step five, during the cooling process, an infrared thermometer can be used to monitor the temperature of the blank. By recording and analyzing the temperature change data, the cooling rate and internal thermal stress of the blank can be understood, so as to determine whether it is in a normal state. For key components or blanks with high quality requirements, ultrasonic testing or X-ray testing can be used for internal defect detection.

[0026] Preferably, the width of the film in step six is ​​determined by the length of the blank, and its thickness range can be controlled by turning process. The film thickness is between 0.1 mm and 1 mm. By adjusting the cutting parameters and the geometry of the tool, the surface roughness and precision of the film can be controlled.

[0027] Beneficial effects of the present invention:

[0028] 1. In the present invention, conductive carbon black or superconductive carbon black powder is added to the UHMW-PE raw material powder and uniformly mixed by a high-speed centrifugal mixing method. The carbon black powder itself has a certain lubricating effect, so that the powder can be directly mixed and processed efficiently and stably, so that the processed black UHMW-PE film not only maintains the original product characteristics, but also increases certain conductivity and UV resistance. At the same time, the adhesion performance with rubber is also improved compared with the ordinary natural color. If high-structure conductive carbon black powder is added to the UHMW-PE raw material powder, the processed black UHMW-PE film has good antistatic properties. Compared with the UHMW-PE film currently used in black rubber tubes and black conveyor belts, which is black, the color of the UHMW-PE film itself is white and translucent. If color is required, the UHMW-PE film is generally mixed with color powder or masterbatch. The UHMW-PE film can not only be quickly mixed and blackened, but also has certain conductivity and UV resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Shown is a flow chart of the production process of the UHMW-PE film with conductive properties of the present invention. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0031] See also Figure 1 The present invention provides an embodiment: a process for producing a UHMW-PE film with conductive properties, the steps of which are as follows:

[0032] Step 1: Raw material preparation

[0033] First, prepare the raw material powder and carbon black powder of UHMW-PE. The carbon black powder can be conductive carbon black or super conductive carbon black.

[0034] Step 2: Mix evenly

[0035] Put the UHMW-PE raw material powder and 3.2%-3.8% carbon black powder into a high-speed centrifugal mixer. Start the high-speed centrifugal mixer. The internal stirring device will rotate at a high speed to generate a strong centrifugal force to fully mix the two powders. The mixing time is between 10-20 minutes, until the powder mixture reaches a uniform black color and there is no obvious particle separation phenomenon;

[0036] Step 3: Powder die casting

[0037] Pour the powder mixture mixed evenly in step 2 into the pre-prepared die-casting mold. After the powder is poured into the mold, a scraper or vibrator is needed to flatten and compact the powder surface to ensure uniform density and size of the blank.

[0038] Step 4: High temperature and high pressure sintering

[0039] The mold filled with powder is placed in a high-temperature and high-pressure sintering furnace for sintering. The sintering temperature is 280 degrees and the pressure is 100 kilograms per square centimeter. Under the combined effects of high temperature and high pressure, the powder particles gradually soften and fuse with each other to form a dense blank.

[0040] Step 5: Natural cooling

[0041] After sintering, the blank is placed in a natural cooling environment for cooling. During the cooling process, the state of the blank needs to be checked regularly to ensure that its internal mechanism is dense and has no obvious defects, so that the blank can be cooled down in a slow and uniform temperature change to avoid internal stress and cracks caused by rapid cooling;

[0042] Step 6: Turning the coil

[0043] The cooled cylindrical blank is put into the machine for turning process. During the processing, the blank is fixed on the lathe, and the cutting tool cuts the blank at a certain speed and feed rate, gradually processing it into the required film thickness. After the cutting is completed, the film is collected and wound into a roll for subsequent storage and transportation.

[0044] Example 1

[0045] When using the process of this technical solution, the steps are as follows:

[0046] Step 1: Raw material preparation

[0047] First, prepare the raw material powder and carbon black powder of UHMW-PE. The carbon black powder can be conductive carbon black.

[0048] Step 2: Mix evenly

[0049] Put the UHMW-PE raw material powder and 3.2% carbon black powder into a high-speed centrifugal mixer. Start the high-speed centrifugal mixer. The internal stirring device will rotate at a high speed to generate a strong centrifugal force to fully mix the two powders. The mixing time is between 10-20 minutes, until the powder mixture reaches a uniform black color and there is no obvious particle separation phenomenon;

[0050] Step 3: Powder die casting

[0051] Pour the powder mixture mixed evenly in step 2 into the pre-prepared die-casting mold. After the powder is poured into the mold, a scraper or vibrator is needed to flatten and compact the powder surface to ensure uniform density and size of the blank. Before pouring the powder mixture, a layer of release agent needs to be applied inside the die-casting mold so that the blank can be demolded smoothly after sintering.

[0052] Step 4: High temperature and high pressure sintering

[0053] Put the mold filled with powder into a high-temperature and high-pressure sintering furnace for sintering. The sintering temperature is 280 degrees and the pressure is 100 kilograms per square centimeter. Under the combined action of high temperature and high pressure, the powder particles gradually soften and fuse with each other to form a dense blank. The sintering time is determined according to the characteristics of the powder and the performance of the sintering furnace. The sintering time ranges from 5 to 12 hours.

[0054] Step 5: Natural cooling

[0055] After sintering is completed, the blank is placed in a natural cooling environment for cooling. During the cooling process, the status of the blank needs to be checked regularly. In the early stage of cooling, due to the rapid temperature change, the inside of the blank may be experiencing a large stress change, so more frequent inspections are required. Set the inspection to be once every hour or every two hours to promptly discover and deal with possible problems. As the blank gradually cools, its internal stress tends to stabilize. At this time, the inspection frequency can be appropriately reduced to once every half a day or every day to ensure that its internal mechanism is dense and has no obvious defects, so that the blank can be cooled down in a slow and uniform temperature change to avoid internal stress and cracks caused by rapid cooling. Visually inspect the appearance of the blank to see if there are cracks, deformation or abnormal color. Use a small hammer to gently tap different parts of the blank. Listen to the sound to judge the density and internal defects of the blank. If the sound is crisp and uniform, it may indicate that the blank is dense inside and has no obvious defects. If the sound is dull or hollow, there may be a problem. During the cooling process, an infrared thermometer can be used to monitor the temperature of the blank. By recording and analyzing the temperature change data, the cooling rate and internal thermal stress of the blank can be understood, so as to judge whether it is in a normal state. For key components or blanks with high quality requirements, ultrasonic testing or X-ray testing can be used for internal defect detection.

[0056] Step 6: Turning the coil

[0057] The cooled cylindrical blank is put on the machine for turning process. During the processing, the blank is fixed on the lathe, and the cutting tool cuts the blank at a certain speed and feed rate, gradually processing it into the required film thickness. After the cutting is completed, the film is collected and wound into a roll for subsequent storage and transportation. The width of the film is determined by the length of the blank, and its thickness range can be controlled by the turning process. The film thickness is between 0.1mm and 1mm. At the same time, adjusting the cutting parameters and the geometry of the tool can control the surface roughness and accuracy of the film.

[0058] Example 2

[0059] When using the process of this technical solution, the steps are as follows:

[0060] Step 1: Raw material preparation

[0061] First, prepare the raw material powder and carbon black powder of UHMW-PE. The carbon black powder can be conductive carbon black.

[0062] Step 2: Mix evenly

[0063] Put the UHMW-PE raw material powder and 3.8% carbon black powder into a high-speed centrifugal mixer. Start the high-speed centrifugal mixer. The internal stirring device will rotate at a high speed to generate a strong centrifugal force to fully mix the two powders. The mixing time is between 10-20 minutes, until the powder mixture reaches a uniform black color and there is no obvious particle separation phenomenon.

[0064] Step 3: Powder die casting

[0065] Pour the powder mixture mixed evenly in step 2 into the pre-prepared die-casting mold. After the powder is poured into the mold, a scraper or vibrator is needed to flatten and compact the powder surface to ensure uniform density and size of the blank. Before pouring the powder mixture, a layer of release agent needs to be applied inside the die-casting mold so that the blank can be demolded smoothly after sintering.

[0066] Step 4: High temperature and high pressure sintering

[0067] Put the mold filled with powder into a high-temperature and high-pressure sintering furnace for sintering. The sintering temperature is 280 degrees and the pressure is 100 kilograms per square centimeter. Under the combined action of high temperature and high pressure, the powder particles gradually soften and fuse with each other to form a dense blank. The sintering time is determined according to the characteristics of the powder and the performance of the sintering furnace. The sintering time ranges from 5 to 12 hours.

[0068] Step 5: Natural cooling

[0069] After sintering is completed, the blank is placed in a natural cooling environment for cooling. During the cooling process, the status of the blank needs to be checked regularly. In the early stage of cooling, due to the rapid temperature change, the inside of the blank may be experiencing a large stress change, so more frequent inspections are required. Set the inspection to be once every hour or every two hours to promptly discover and deal with possible problems. As the blank gradually cools, its internal stress tends to stabilize. At this time, the inspection frequency can be appropriately reduced to once every half a day or every day to ensure that its internal mechanism is dense and has no obvious defects, so that the blank can be cooled down in a slow and uniform temperature change to avoid internal stress and cracks caused by rapid cooling. Visually inspect the appearance of the blank to see if there are cracks, deformation or abnormal color. Use a small hammer to gently tap different parts of the blank. Listen to the sound to judge the density and internal defects of the blank. If the sound is crisp and uniform, it may indicate that the blank is dense inside and has no obvious defects. If the sound is dull or hollow, there may be a problem. During the cooling process, an infrared thermometer can be used to monitor the temperature of the blank. By recording and analyzing the temperature change data, the cooling rate and internal thermal stress of the blank can be understood, so as to judge whether it is in a normal state. For key components or blanks with high quality requirements, ultrasonic testing or X-ray testing can be used for internal defect detection.

[0070] Step 6: Turning the coil

[0071] The cooled cylindrical blank is put on the machine for turning process. During the processing, the blank is fixed on the lathe, and the cutting tool cuts the blank at a certain speed and feed rate, gradually processing it into the required film thickness. After the cutting is completed, the film is collected and wound into a roll for subsequent storage and transportation. The width of the film is determined by the length of the blank, and its thickness range can be controlled by the turning process. The film thickness is between 0.1mm and 1mm. At the same time, adjusting the cutting parameters and the geometry of the tool can control the surface roughness and accuracy of the film.

[0072] Example 3

[0073] When using the process of this technical solution, the steps are as follows:

[0074] Step 1: Raw material preparation

[0075] First, prepare the raw material powder and carbon black powder of UHMW-PE. The carbon black powder can be superconductive carbon black.

[0076] Step 2: Mix evenly

[0077] Put the UHMW-PE raw material powder and 3.5% carbon black powder into a high-speed centrifugal mixer. Start the high-speed centrifugal mixer. The internal stirring device will rotate at a high speed to generate a strong centrifugal force to fully mix the two powders. The mixing time is between 10-20 minutes, until the powder mixture reaches a uniform black color and there is no obvious particle separation phenomenon.

[0078] Step 3: Powder die casting

[0079] Pour the powder mixture mixed evenly in step 2 into the pre-prepared die-casting mold. After the powder is poured into the mold, a scraper or vibrator is needed to flatten and compact the powder surface to ensure uniform density and size of the blank. Before pouring the powder mixture, a layer of release agent needs to be applied inside the die-casting mold so that the blank can be demolded smoothly after sintering.

[0080] Step 4: High temperature and high pressure sintering

[0081] Put the mold filled with powder into a high-temperature and high-pressure sintering furnace for sintering. The sintering temperature is 280 degrees and the pressure is 100 kilograms per square centimeter. Under the combined action of high temperature and high pressure, the powder particles gradually soften and fuse with each other to form a dense blank. The sintering time is determined according to the characteristics of the powder and the performance of the sintering furnace. The sintering time ranges from 5 to 12 hours.

[0082] Step 5: Natural cooling

[0083] After sintering is completed, the blank is placed in a natural cooling environment for cooling. During the cooling process, the status of the blank needs to be checked regularly. In the early stage of cooling, due to the rapid temperature change, the inside of the blank may be experiencing a large stress change, so more frequent inspections are required. Set the inspection to be once every hour or every two hours to promptly discover and deal with possible problems. As the blank gradually cools, its internal stress tends to stabilize. At this time, the inspection frequency can be appropriately reduced to once every half a day or every day to ensure that its internal mechanism is dense and has no obvious defects, so that the blank can be cooled down in a slow and uniform temperature change to avoid internal stress and cracks caused by rapid cooling. Visually inspect the appearance of the blank to see if there are cracks, deformation or abnormal color. Use a small hammer to gently tap different parts of the blank. Listen to the sound to judge the density and internal defects of the blank. If the sound is crisp and uniform, it may indicate that the blank is dense inside and has no obvious defects. If the sound is dull or hollow, there may be a problem. During the cooling process, an infrared thermometer can be used to monitor the temperature of the blank. By recording and analyzing the temperature change data, the cooling rate and internal thermal stress of the blank can be understood, so as to judge whether it is in a normal state. For key components or blanks with high quality requirements, ultrasonic testing or X-ray testing can be used for internal defect detection.

[0084] Step 6: Turning the coil

[0085] The cooled cylindrical blank is put on the machine for turning process. During the processing, the blank is fixed on the lathe, and the cutting tool cuts the blank at a certain speed and feed rate, gradually processing it into the required film thickness. After the cutting is completed, the film is collected and wound into a roll for subsequent storage and transportation. The width of the film is determined by the length of the blank, and its thickness range can be controlled by the turning process. The film thickness is between 0.1mm and 1mm. At the same time, adjusting the cutting parameters and the geometry of the tool can control the surface roughness and accuracy of the film.

[0086] Example 4

[0087] When using the process of this technical solution, the steps are as follows:

[0088] Step 1: Raw material preparation

[0089] First, prepare the raw material powder and carbon black powder of UHMW-PE. The carbon black powder can be high-structure conductive carbon black.

[0090] Step 2: Mix evenly

[0091] Put the UHMW-PE raw material powder and 3.5% carbon black powder into a high-speed centrifugal mixer. Start the high-speed centrifugal mixer. The internal stirring device will rotate at a high speed to generate a strong centrifugal force to fully mix the two powders. The mixing time is between 10-20 minutes, until the powder mixture reaches a uniform black color and there is no obvious particle separation phenomenon.

[0092] Step 3: Powder die casting

[0093] Pour the powder mixture mixed evenly in step 2 into the pre-prepared die-casting mold. After the powder is poured into the mold, a scraper or vibrator is needed to flatten and compact the powder surface to ensure uniform density and size of the blank. Before pouring the powder mixture, a layer of release agent needs to be applied inside the die-casting mold so that the blank can be demolded smoothly after sintering.

[0094] Step 4: High temperature and high pressure sintering

[0095] Put the mold filled with powder into a high-temperature and high-pressure sintering furnace for sintering. The sintering temperature is 280 degrees and the pressure is 100 kilograms per square centimeter. Under the combined action of high temperature and high pressure, the powder particles gradually soften and fuse with each other to form a dense blank. The sintering time is determined according to the characteristics of the powder and the performance of the sintering furnace. The sintering time ranges from 5 to 12 hours.

[0096] Step 5: Natural cooling

[0097] After sintering is completed, the blank is placed in a natural cooling environment for cooling. During the cooling process, the status of the blank needs to be checked regularly. In the early stage of cooling, due to the rapid temperature change, the inside of the blank may be experiencing a large stress change, so more frequent inspections are required. Set the inspection to be once every hour or every two hours to promptly discover and deal with possible problems. As the blank gradually cools, its internal stress tends to stabilize. At this time, the inspection frequency can be appropriately reduced to once every half a day or every day to ensure that its internal mechanism is dense and has no obvious defects, so that the blank can be cooled down in a slow and uniform temperature change to avoid internal stress and cracks caused by rapid cooling. Visually inspect the appearance of the blank to see if there are cracks, deformation or abnormal color. Use a small hammer to gently tap different parts of the blank. Listen to the sound to judge the density and internal defects of the blank. If the sound is crisp and uniform, it may indicate that the blank is dense inside and has no obvious defects. If the sound is dull or hollow, there may be a problem. During the cooling process, an infrared thermometer can be used to monitor the temperature of the blank. By recording and analyzing the temperature change data, the cooling rate and internal thermal stress of the blank can be understood, so as to judge whether it is in a normal state. For key components or blanks with high quality requirements, ultrasonic testing or X-ray testing can be used for internal defect detection.

[0098] Step 6: Turning the coil

[0099] The cooled cylindrical blank is put on the machine for turning process. During the processing, the blank is fixed on the lathe, and the cutting tool cuts the blank at a certain speed and feed rate, gradually processing it into the required film thickness. After the cutting is completed, the film is collected and wound into a roll for subsequent storage and transportation. The width of the film is determined by the length of the blank, and its thickness range can be controlled by the turning process. The film thickness is between 0.1mm and 1mm. At the same time, adjusting the cutting parameters and the geometry of the tool can control the surface roughness and accuracy of the film.

[0100] Through the above steps, the present invention adds conductive carbon black or superconductive carbon black powder to the UHMW-PE raw material powder and uniformly mixes it by high-speed centrifugal mixing. The carbon black powder itself has a certain lubricating effect, so that the powder can be directly mixed and processed efficiently and stably, so that the processed black UHMW-PE film not only maintains the original product characteristics, but also increases certain conductivity and UV resistance. At the same time, the adhesion performance with rubber is also improved compared with the ordinary natural color. If high-structure conductive carbon black powder is added to the UHMW-PE raw material powder, the processed black UHMW-PE film has good antistatic performance, so as to solve the problem that the existing black UHMW-PE film is mixed with color powder or masterbatch for coloring, and its uniformity will be relatively poor, and the overall conductivity, UV resistance and adhesion performance with rubber cannot meet the needs of users.

[0101] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the spirit of the present invention.

Claims

1. A process for producing a UHMW-PE film having conductive properties, characterized in that: The steps are as follows: Step 1: Raw material preparation First, prepare the raw material powder and carbon black powder of UHMW-PE. The carbon black powder can be conductive carbon black or super conductive carbon black. Step 2: Mix evenly Put the UHMW-PE raw material powder and 3.2%-3.8% carbon black powder into a high-speed centrifugal mixer. Start the high-speed centrifugal mixer. The internal stirring device will rotate at a high speed to generate a strong centrifugal force to fully mix the two powders. The mixing time is between 10-20 minutes, until the powder mixture reaches a uniform black color and there is no obvious particle separation phenomenon; Step 3: Powder die casting Pour the powder mixture mixed evenly in step 2 into the pre-prepared die-casting mold. After the powder is poured into the mold, a scraper or vibrator is needed to flatten and compact the powder surface to ensure uniform density and size of the blank. Step 4: High temperature and high pressure sintering The mold filled with powder is placed in a high-temperature and high-pressure sintering furnace for sintering. The sintering temperature is 280 degrees and the pressure is 100 kilograms per square centimeter. Under the combined effects of high temperature and high pressure, the powder particles gradually soften and fuse with each other to form a dense blank. Step 5: Natural cooling After sintering, the blank is placed in a natural cooling environment for cooling. During the cooling process, the state of the blank needs to be checked regularly to ensure that its internal mechanism is dense and has no obvious defects, so that the blank can be cooled down in a slow and uniform temperature change to avoid internal stress and cracks caused by rapid cooling; Step 6: Turning the coil The cooled cylindrical blank is put into the machine for turning process. During the processing, the blank is fixed on the lathe, and the cutting tool cuts the blank at a certain speed and feed rate, gradually processing it into the required film thickness. After the cutting is completed, the film is collected and wound into a roll for subsequent storage and transportation.

2. The process for producing a UHMW-PE film having conductive properties according to claim 1, characterized in that: Carbon black powder can also be selected from highly structured conductive carbon black.

3. The process for producing a UHMW-PE film having conductive properties according to claim 1, characterized in that: In step 3, before pouring the powder mixture, a layer of release agent needs to be applied inside the die-casting mold so that the sintered blank can be demoulded smoothly.

4. The process for producing a UHMW-PE film having conductive properties according to claim 1, characterized in that: The sintering time in step 4 is determined according to the characteristics of the powder and the performance of the sintering furnace, and the sintering time ranges from 5 to 12 hours.

5. The process for producing a UHMW-PE film having conductive properties according to claim 1, characterized in that: In step 5, due to the rapid temperature change at the initial stage of cooling, the inside of the blank may be experiencing a large stress change, so more frequent inspections are required, set to check once every hour or every two hours, so as to promptly discover and deal with possible problems.

6. The process for producing a UHMW-PE film having conductive properties according to claim 5, characterized in that: In step 5, as the blank gradually cools, its internal stress tends to stabilize. At this time, the inspection frequency can be appropriately reduced to once every half a day or every day.

7. The process for producing a UHMW-PE film having conductive properties according to claim 1, characterized in that: In step five, you need to visually inspect the appearance of the blank to see if there are cracks, deformation or abnormal color. Use a small hammer to gently tap different parts of the blank and judge the density and internal defects of the blank by listening to the sound. If the sound is crisp and uniform, it may indicate that the blank is dense inside and has no obvious defects. If the sound is dull or hollow, there may be a problem.

8. The process for producing a UHMW-PE film with conductive properties according to claim 7, characterized in that: Step 5: During the cooling process, an infrared thermometer can be used to monitor the temperature of the blank. By recording and analyzing the temperature change data, the cooling rate and internal thermal stress of the blank can be understood, so as to determine whether it is in a normal state. For key components or blanks with high quality requirements, ultrasonic testing or X-ray testing can be used for internal defect detection.

9. The process for producing a UHMW-PE film having conductive properties according to claim 1, characterized in that: In step six, the width of the film is determined by the length of the blank, and its thickness range can be controlled by the turning process. The film thickness is between 0.1 mm and 1 mm. By adjusting the cutting parameters and the geometry of the tool, the surface roughness and precision of the film can be controlled.